Comparative Analysis of PT KAI (Persero) Financial Performance for the 2020-2023 Period Using Profitability Ratios - Sriwiyanti, Eva; Nikitria, Athina (Program Studi Akuntansi Universitas Simalungun, 2024)
This study aims to analyze the financial performance of PT Kereta Api Indonesia during the period 2020-2023. In 2020 to 2021, the impact of the COVID-19 pandemic caused a significant decline in the company's profits due to limited mobility and travel restrictions. However, the research findings showed a significant recovery and increase in profits in 2022-2023 as restrictions eased and economic activity increased. This research uses a quantitative method combined with comparative descriptive analysis. This research utilizes secondary data, which is information collected by third parties or sources for specific purposes. The main emphasis in the analysis is done through profitability ratios, which reflect the effectiveness of the company in generating profits. A comparative approach is used to compare financial performance from year to year to identify significant changes during and after the pandemic. This research also differs from previous studies as it not only examines a more recent time period, but also uses a comparative approach with a focus on profitability ratio analysis. The results of this study are expected to provide insights for companies in formulating more adaptive and sustainable financial strategies in the future.